Increasing Brand Awareness of Petra Production House through Instagram Feeds - Nicholas; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2026)
The writers aimed at helping a movie production company called Petra Production House (PPH) under the management of Faculty of Humanities and Creative Industries, Petra Christian University. After discussion with the representative of PPH, it was found that PPH lacks resources in digital marketing. Therefore, PPH has not performed well in promoting its brand on Instagram. Ultimately, the client wants the writers to improve PPH’s Instagram feeds quality. After conducting a survey, most respondents answered that they did not recognize PPH and thought the overall Instagram feeds were uninteresting. To solve this, the writers proposed a solution in improving the quality of PPH’s Instagram feeds by focusing on PPH’s Instagram posts, stories, captions, and hashtags. The writers used the respondents’ answers and theories of social media copywriting (Bly, 2020) and typography (Büyükpehli̇van, 2024) among others. After the implementation of the solution, the writers found that it had a positive impact.